2009
DOI: 10.1097/gco.0b013e32832a0654
|View full text |Cite
|
Sign up to set email alerts
|

Local injury to the endometrium: its effect on implantation

Abstract: Local injury to endometria of IVF patients in controlled ovarian hyperstimulation cycle may increase the incidence of embryo implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 19 publications
3
74
0
4
Order By: Relevance
“…The production of the injury-induced cytokines IP10, MCP1, and CCL4 was shown to be regulated by estrogen (Boucher et al 2000, Kitaya et al 2003, Sentman et al 2004, Carlino et al 2008. Local injury of the endometrium during the proliferative phase of the menstrual cycle substantially increases endometrial expression of estrogen receptors in the following secretory phase (Li & Hao 2009). Therefore, this reciprocal regulation of estrogen and pro-inflammatory cytokines may indicate that the estrogen-induced proliferation in the endometrium is mediated by cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The production of the injury-induced cytokines IP10, MCP1, and CCL4 was shown to be regulated by estrogen (Boucher et al 2000, Kitaya et al 2003, Sentman et al 2004, Carlino et al 2008. Local injury of the endometrium during the proliferative phase of the menstrual cycle substantially increases endometrial expression of estrogen receptors in the following secretory phase (Li & Hao 2009). Therefore, this reciprocal regulation of estrogen and pro-inflammatory cytokines may indicate that the estrogen-induced proliferation in the endometrium is mediated by cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, the rate of successful implantation in patients with endometrial trauma was 10.9% while the rate of success in the control group was 3.38% (4). In another research performed by Li et al in the Infertility Department of Shenzhen University of China it was found out that local endometrial trauma leads to an increase in the success of implantation in IVF patients (7). In a study by Zhou et al in the Infertility Department of Shenzhen University of China, a number of IVF patients were examined.…”
Section: Discussionmentioning
confidence: 94%
“…This improvement in implantation after endometrial injury can be explained by 3 suggestions. First postulation is the increased decidualization in response to local injury [4]. Second hypothesis, the considerable increase in the release of cytokines, interleukins, growth factors, macrophages, and dendritic cells with endometrial healing, all of which are of benefit in the process of implantation [4] [5].…”
Section: Et Al In 2003 Was the Very Firstmentioning
confidence: 99%
“…First postulation is the increased decidualization in response to local injury [4]. Second hypothesis, the considerable increase in the release of cytokines, interleukins, growth factors, macrophages, and dendritic cells with endometrial healing, all of which are of benefit in the process of implantation [4] [5]. Third is the accelerated maturation of the endometrium in response to controlled ovarian stimulation during ART [6].…”
Section: Et Al In 2003 Was the Very Firstmentioning
confidence: 99%